A clinical pharmacokinetic and pharmacodynamic study of salbutamol in prophylaxis of bronchial asthma - Le Roux-Nel, Anna Maria (Stellenbosch : Stellenbosch University, 2012)
Dissertations (D. Phil.) -- University of Stellenbosch, 1998.